Cultural Aspects in Sustainable Development: The Dayak Tribe in East Kalimantan - Hardian*, Gagas Tegar; Kusdiwanggo, Susilo; Arsita, Ema Dwi (Universitas Syiah Kuala, 2024)
Sustainable development is the goal of the SDG's, where cultural aspects can influence other aspects of life. Tribes in Indonesia also help to achieve SDG's from a cultural aspect, one of which is the Dayak Tribe. The Dayak tribe has local wisdom in the form of culture that is maintained to carry out the process of life. The Dayak tribe maintains various cultures that continue to this day as a form of concern for the surrounding environment. The cultural aspects applied by the Dayak people in carrying out their lives as a form of sustainable development. This research is a descriptive study through a library approach. The theory in this study uses cultural aspects in sustainable development. The findings of this research relate the cultural aspects that support the achievement of the cultural pillars as the 4 pillars of the SDGs.